François Rosset, Dominique Triaire, Jan Potocki. Biografia, tł. Anna Wasilewska, WAB, Warszawa 2006, ss. 517 / Anna Łysiak-Łątkowska. - Łysiak, Anna (historyk)
Recenzja książki: Jan Potocki. Biografia / François Rosset, Dominique Triaire. - Warszawa, 2006.